Bilinear approximations to the mixed-mode I–II delamination cohesive law using an inverse method. (April 2015) - de Morais, A.B.; Pereira, A.B.; de Moura, M.F.S.F.; Silva, F.G.A.; Dourado, N.
Abstract: This paper presents an experimental and numerical study of the mixed-mode I–II delamination of unidirectional carbon/epoxy laminates. Double cantilever beam, end-notched flexure and mixed-mode bending tests were conducted in order to cover the full range of mode-mix combinations. Finite element cohesive zone models with a bilinear softening cohesive law were subsequently employed to fit experimental load–displacement curves. This required a genetic algorithm to find optimal bilinear softening parameters. Good agreement was achieved between predicted and experimental curves. Furthermore, the bilinear softening parameters showed consistent variations with the global mode-mix that could be interpreted in terms of local damage mechanisms. Nevertheless, further research is needed to define mixed-mode tractions and separations leading to a unique cohesive law.